1996
DOI: 10.1074/jbc.271.13.7257
|View full text |Cite
|
Sign up to set email alerts
|

Doc2 Enhances Ca2+-dependent Exocytosis from PC12 Cells

Abstract: We previously isolated a new protein having two C2-like domains which interacted with Ca 2؉ and phospholipid and named Doc2 (Double C2). Because Doc2 was abundantly expressed in brain where it was highly concentrated on the synaptic vesicle fraction, we have examined here whether Doc2 is involved in Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 39 publications
3
66
0
Order By: Relevance
“…We have previously shown that, in order to shift the distribution of chromaffin-granule membranes, the organelles in a large-granule fraction can be lysed ; the granule membranes are then distributed in markedly less dense fractions when run on a 0.3-1.2 M sucrose gradient [17]. Following this procedure, granule membranes, indicated by the presence of DβH and synaptophysin ( Figures 3A and 3B), were found in less dense fractions than expected for intact granules, and were clearly separated from membranes containing Doc2, which remained in the denser fractions (9)(10)(11)(12)(13)(14) on this gradient (Figures 3A and 3B). There was little evidence for any intact granules remaining on the gradient, as little or no synaptophysin (an integral membrane component of SLMVs and chromaffin granules) was detected in fractions 12-14.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that, in order to shift the distribution of chromaffin-granule membranes, the organelles in a large-granule fraction can be lysed ; the granule membranes are then distributed in markedly less dense fractions when run on a 0.3-1.2 M sucrose gradient [17]. Following this procedure, granule membranes, indicated by the presence of DβH and synaptophysin ( Figures 3A and 3B), were found in less dense fractions than expected for intact granules, and were clearly separated from membranes containing Doc2, which remained in the denser fractions (9)(10)(11)(12)(13)(14) on this gradient (Figures 3A and 3B). There was little evidence for any intact granules remaining on the gradient, as little or no synaptophysin (an integral membrane component of SLMVs and chromaffin granules) was detected in fractions 12-14.…”
Section: Resultsmentioning
confidence: 99%
“…The only functional data on Doc2 in regulated exocytosis comes from a study on PC12 cells [12], and so we also examined the distribution of Doc2, compared with SLMVs, dense-core granules, mitochondria and endosomes, in this cell type. This was initially examined by fractionation of a PC12 PNS on a 0.6-1.8 M sucrose gradient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations